Multi‐Center, Community‐Based Cardiac Implantable Electronic Devices Registry: Population, Device Utilization, and Outcomes. Issue 3 (March 2016) - Gupta, Nigel; Kiley, Mary Lou; Anthony, Faith; Young, Charlie; Brar, Somjot; Kwaku, Kevin
Abstract : Background: The purpose of this study is to describe key elements, clinical outcomes, and potential uses of the Kaiser Permanente–Cardiac Device Registry. Methods and Results: This is a cohort study of implantable cardioverter defibrillators (ICD), pacemakers (PM), and cardiac resynchronization therapy (CRT) devices implanted between January 1, 2007 and December 31, 2013 by ≈400 physicians in 6 US geographical regions. Registry data variables, including patient characteristics, comorbidities, indication for procedures, complications, and revisions, were captured using the healthcare system's electronic medical record. Outcomes were identified using electronic screening algorithms and adjudicated via chart review. There were 11 924 ICDs, 33 519 PMs, 4472 CRTs, and 66 067 leads registered. A higher proportion of devices were implanted in males: 75.1% (ICD), 55.0% (PM), and 66.7% (CRT), with mean patient age 63.2 years (ICD), 75.2 (PM), and 67.2 (CRT). The 30‐day postoperative incidence of tamponade, hematoma, and pneumothorax were ≤0.3% (ICD), ≤0.6% (PM), and ≤0.4% (CRT). Device failures requiring revision occurred at a rate of 2.17% for ICDs, 0.85% for PMs, and 4.93% for CRTs, per 100 patient observation years. Superficial infection rates were <0.03% for all devices; deep infection rates were 0.6% (ICD), 0.5% (PM), and 1.0% (CRT). Results were used to monitor vendor‐specific variations and were systematically shared with individual regions to address potential variations in outcomes, utilization, and to assist with the management of device recalls. Conclusions: The Kaiser Permanente–Cardiac Device Registry is a robust tool to monitor postprocedural patient outcomes and postmarket surveillance of implants and potentially change practice patterns.